45 Comparing impact of an e-learning package to lecture-based teaching in the management of of Supraventricular Tachycardia(SVT): a randomized-controlled study. (May 2019) - Mohee, Kevin; Haboubi, Hasan; Protty, Majd; Srinivasan, Christopher; Townend, William; Weston, Clive
Abstract : Introduction: To compare the impact of e-learning package and theoretical teaching on the ability of both graduate and undergraduate medical students to learn the management of supraventricular tachycardia (SVT). Methods: We conducted a randomized controlled blinded study at two medical schools in Wales, UK. Participants included graduate-entry medical students from Swansea University and undergraduate medical students from Cardiff University. The intervention consisted of one hour of training using an e-learning package versus an hour of lecture based teaching. The outcome was comparison within each groups and between groups of mean scores using a pre-intervention and immediate post-intervention questionnaire. Another questionnaire was e-mailed after 2 weeks and mean scores were again compared to baseline, immediate post intervention between each groups and within each groups. The hypothesis was an improved outcome in the intervention group. Randomization was 1 to 1. Results: Of the 97 participants available for randomization, 46 underwent teaching using the e-learning package and 51 were taught in the lecture group. Mean scores were higher in the e-learning package group than the lecture group, though this difference was not statistically significant (3.63 vs. 3.37; P = 0.085) immediately after intervention. At 2-weeks post intervention, mean scores in the e-learning package group was significantly higher than the mean scores in the lecture group (3.59 vs. 2.86; P = 0.002). This was despite a sub-analysis of the results demonstrating that subjects in the lecture group had seen more cases which was statistically significant compared to those in the e-learning group (32 vs. 13; P = 0.002). Conclusion: E-learning seems to be the preferred method of learning and the method that confers longer retention time for both post-graduate and undergraduate medical students. Conflict of Interest: None